Metabolomic profiles of tropical Chlorella species in response to physiological changes during nitrogen deprivation - Vello, Vejeysri; Chu, Wan Loy; Lim, Phaik Eem; Majid, Nazia Abdul; Phang, Siew Moi (Springer Verlag, 2018)
Chlorella species are known to be potential algal candidates for biodiesel production due to their ability to store lipids and their natural metabolic versatility. This study assessed the photosynthetic performance, biochemical composition, and metabolomic profiles of tropical Chlorella UMACC050 harvested from different growth phases in batch culture, grown under nitrogen-replete, and nitrogen-depleted conditions. Physiological data suggested that growth and photosynthetic efficiency were affected during nitrogen deprivation. Nitrogen deprivation resulted in a decrease in biomass productivity and an increase of lipid content. Nitrogen-depletion resulted in an increase in saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA), especially C16:0, C18:0, and C18:1, at the expense of polyunsaturated fatty acids (PUFA). Changes in the metabolomic profiles suggested that there was nitrogen assimilation from proteins and photosynthetic machinery, together with repartitioning of carbon into carbohydrates and lipids in response to nitrogen depletion. Overall, our results expand the current understanding of metabolomics of Chlorella species and provide valuable insights into their lipid accumulation during nitrogen deprivation, which is important for optimization of lipid productivity in the tropical environment.